The impact of COVID disease on agriculture 19 - Ashutosh Yadav (Journal of Advanced Research in Entrepreneurship, Innovation and SME Management, 2021)
The different pandemics that humanity has experienced, like the Spanish Flu, Asian Flu, Hong Kong Flu, HIV/AIDS, SARS, Ebola, and swine influenza, have had an excellent impact on the economy, the environment, and any act, like livestock, agriculture, tourism, transport, education, health, fishing, mining, industrial, commerce, etc. Currently, humanity is facing another pandemic, the infection of the new coronavirus (2019-nCoV) that generates the disease known as COVID-19. The objective of this documents analyze and discuss the effects in agriculture of events related to the disease of COVID-19. For this analysis, data from the Food Agriculture Organization (FAO), the planet Health Organization (WHO) and scientific and technical documents are used. There is sufficient evidence to affirm that the pandemic caused by the COVID-19 disease has a crucial effect on agriculture and therefore the food supply chain, mainly affecting food demand and consequently food security, with a great impact on the most vulnerable population. How to cite this article: Yadav A, Yadav M. The Impact of COVID-19 Disease on Agriculture. J Adv Res Entrep Innov SMES Mgmt 2021; 4(1): 10-11